An educational software design critiquing tool to support software design course - Mohd Ali, Norhayati; Admodisastro, Novia Indriaty; Abdulkareem , Soran Mahmood (IEEE (IEEE Xplore), 2013)
Teaching and learning for software design course at universities demands a sufficient supervision from the educators (e.g., instructors, lecturers, teachers, mentors and others) and also active communications between students and lecturers. With adequate practice of software design problems/exercises, it can enhance students' knowledge in software design. A good software designer requires both the acquisition of theory and practice of skills under the guidance of a lecturer. However, this is not feasible in the conventional classroom learning setting. The amount of contact hours between the lecturers and students is very limited. Hence, it constrains the amount of guidance and learning that students may obtain in a course. Thus, we propose a software design critiquing tool to support the students in practicing the software design problems/exercises. The aim of this paper is to describe the use of a critiquing-based approach in a software design tool for supporting the teaching and learning of a software design course. We believe that a software design critiquing tool would enhance the students' learning and knowledge of software design. In addition, it would complement the teaching and learning performed in a conventional classroom setting.